MR Imaging in Diagnosis of Pelvic Floor Descent: Supine versus Sitting Position - Francesca Iacobellis; Antonio Brillantino; Adolfo Renzi; Luigi Monaco; Nicola Serra; Beatrice Feragalli; Aniello Iacomino; Luca Brunese; Salvatore Cappabianca (Gastroenterology Research and Practice)
Introduction. Functional disorders of the pelvic floor represent have a significant impact on the quality of life. The advent of open-configuration systems allowed for the evaluation of defecation with MR imaging in sitting position. The purpose of the present study is to compare the results of static and dynamic pelvic MR performed in supine position versus sitting position, using a new MR prototype machine, in the diagnosis of pelvic floor descent. Materials and Methods. Thirty-one patients with pelvic floor disorders were enrolled, and underwent MR Defecography in supine position with 1.5 T closed magnet (MAGNETOM Symphony, Siemens, Germany) and in sitting position with a 0.25-Tesla open magnet system (G-Scan ESAOTE, Italy). Results. In rest and squeezing phases, positions of bladder, vagina, and ARJ were significantly different when the patient was imaged in supine versus sitting position. In the defecation phase, a significant difference for the bladder and vagina position was detected between the two exams whereas a significant difference for the ARJ was not found. A statistically significant difference exists when the pelvic floor descent is evaluated in sitting versus supine position. Conclusion. Our results show that MR Defecography in sitting position may represent a useful tool to correctly diagnose and grade the pelvic organ descent.